A Rare Case of Klippel Feil Syndrome Associated with Mirror Movements: Life Sciences-Pediatrics - S, Dr. Sundari; V S, Dr. Hamsa; R, Dr. Ramya (International Journal of Life Science and Pharma Research, 2024)
Klippel Feil Syndrome (KFS) is a multisystem disorder with the typical clinical trial of short neck, restriction of headand neck movements and low posterior hairline and associated with anomalies of the urogenital, musculoskeletal, neurological andcardiovascular systems. Here is a case report of a young boy with history of abnormal head and upper limbs movements alongwith repeated bowing of head since the age of 6 months. He also had frequent falls with repeated minor trauma to the face.Antenatal and peripartum period was uneventful and child had no neonatal complications with normal development. Onexamination the child had abnormal head position with bowing, short neck and low hair line. Musculoskeletal system examinationrevealed decreased range of passive movements at cervical spine extension and lateral flexion with no focal neurological deficits.Further examination revealed Mirror movements (synkinesis) in the upper limbs. Mirror movements are the involuntarymovements of one body part that mirror intentional movements on the opposite side. Other Systemic examinations were normal.CT Cervical spine showed fusion of the upper three cervical vertebrae and the child was diagnosed as a case of klippel feil syndrometype 2 presenting with mirror movements. This rare case of klippel feil syndrome is being presented with the aim that such casesshould be detected and treated at an early stage to reduce the cosmetic & social stigma to the patient and parents. This casereport also gives a brief overview of associated features of KFS along with its management.